Strategi Pemasaran Pembiayaan Warung Mikro Bank Syariah Mandiri KC. Kendal - Akhmad Nurasikin (Jurnal Iqtisad, 2019)
Abstract The development of Micro Small Enterprises (SMEs) annually increasing. This is due to the high interest of the community, especially the SMEs who want to start a business. One of the problems faced is the limited capital owned. Bank Syariah Mandiri (BSM) is present as a solution to answer the capital problems of SMEs by offering microfinance through Micro Stalls (Warung Mikro). This study aims to find out how the implications of the marketing strategy are with the approach to the marketing mix (product, price, place and promotion) of BSM micro stalls and analyze their strengths and weaknesses. Based on the results of research conducted by the author, that the marketing strategy carried out has positive implications for the progress of the business of its customers and increases the financing portfolio of Micro Stalls, BSM KC, Kendal. The advantages of the products include Principles and agreements in accordance with the Shari'ah, Limit of financing in accordance with micro segments, The process of applying for financing is relatively easy and fast, minor installments and fixed to maturity, business training and assistance programs for MSEs, using an individual approach and ball pick up system and is located in a area that is relatively close to the micro segment business location. While the disadvantages of financing Micro Stalls, BSM KC, Kendal, among others; the lack of employees who master shari'ah transactions, inadequate facilities and promotions is still monotonous so it is less efficient.